Resource-saving management paradigm in projects of Rosatom State Corporation machine-building division enterprises - Golovko, M. V.; Potyavin, A. M.; Ukhalina, I. A.; Antsibor, A. V.; Efimenko, N. A.; Rogacheva, Z. S. (Глобальная ядерная безопасность, 2023)
The article analyzes current problems and successful practices of implementing lean technologies at Russian enterprises. The purpose of the presented research work is to develop relevant mechanisms, search for tools and technologies with the help of which the mentioned problems (general and specific) can be overcome. The novelty of the research lies in the justification of the transition to a new paradigm of resource-saving management and adaptation of project management and business analysis tools to the projects of lean technology implementation. To investigate the trends in the formation of a new management paradigm based on the active involvement of resource-saving tools, such general scientific methods as analysis of scientific and specialized literature, synthesis, logical and analytical methods were used. Materials of internal reporting of the enterprises of the machine-building division of Rosatom State Corporation are used in the work. The main problems of implementing lean technologies at Russian enterprises are formulated and ranked. The list of enterprise management techniques in accordance with the new management paradigm is presented, as well as their capabilities to improve the efficiency of management decisions. The importance of digital technologies for ensuring the effectiveness of resource-saving projects is substantiated. An approximate strategic map for nuclear power engineering enterprises, based on the balanced scorecard methodology, in the implementation of lean decisions is developed. The most effective projects of enterprises of the machine-building division of the State Atomic Energy Corporation ROSATOM were identified, which can become benchmarking objects for scaling experience among enterprises of other divisions of the State Corporation, as well as for enterprises of other industries and spheres of activity. Despite the rather high degree of development of the problem of lean technology implementation, new realities form specific factors that can make the previous scientific and practical results irrelevant. Further research of this topic should be carried out on the basis of analyzing the dynamics of the external environment leading to fluctuations in the industry and regional markets.